A REVIS ED UNDERSTANDING OF ENGINEERING PROG NOSTICS - Stenly Tangkuman (Jurnal Tekno Mesin, 2016)
Much of the understanding of prognostics currently appeared is scattered among manypublication . Actually,m ost researchers have developed their own understanding of prognostics , and there are some divergences inliterature . Firstly, t his work reviews the qualified publication that explain ed their understanding aboutprognostics in engineering application. Then, this paper has been prepared a revi sed understanding ofengineering prognostics. However, it is hoped that this paper will provide the researchers with alternativeprognostics’s under standing in use, and will be convenient when prognostics problem have to be solved.Keywords:prognostics, failure